EF24 prevents rotenone‐induced estrogenic status alteration in breast cancer. (31st December 2013) - Roy, Debarshi; Kabiraj, Parijat; Pal, Rituraj
Abstract Protein disulfide isomerase (PDI), an important endoplasmic reticulum‐resident oxidoreductase chaperone can bind to estrogens as well as intact with its receptor proteins [i.e. estrogen receptors (ER) α and β]. It has been postulated that PDI also acts as an intracellular 17β‐estradiol (E2)‐binding protein that transports and accumulates E2 in live cells. Drop in E2 level promotes dissociation of E2 from PDI and released in cytosol; the released E2 can augment estrogen receptor‐mediated transcriptional activity and mitogenic action in cultured cells by modulating the ERβ/ERα ratio. In this study, we observed rotenone‐induced damage to PDI leads to significant increase in ERβ/ERα ratio by down‐regulating ERα and up‐regulating ERβ. We demonstrated that nitrosative stress induced disruption of the cellular estrogenic status can be prevented through diphenyl difluoroketone (EF24, curcumin analog) intervention by protecting PDI from reactive oxygen species (ROS)‐induced damage. Together, our study suggests that both PDI and EF24 can play a vital role in maintaining cellular estrogenic homeostasis.